Implementation of Dysmenorrhea Exercises in the Morning Before Learning about Menstrual Pain in Female Students - Putri, Maidina; Nurhayati, Nurhayati; Rahmat, Rezqiqah Aulia; Almujahidiani, Titik; Lubis, Halimatussakdiyah (International Journal of Health Sciences, 2024)
Dysmenorrhea is one of the most common gynecological problems and can affect more than 50% of women causing the inability to perform daily activities for 1 to 3 days each month. Absenteeism in adolescents from school is one of the consequences of primary dysmenorrhea reaching approximately 25%. Dysmenorrhea is caused by increased prostaglandin hormones, increased prostaglandin hormones are caused by decreased estrogen and progesterone hormones causing the endometrium to swell and die because it is not fertilized. Increased prostaglandin hormones cause uterine muscles to contract and produce pain. The purpose of this study was to determine the effectiveness of morning dysmenorrhea exercises in treating menstrual pain in adolescent girls during menstruation at SMK TRIS Maros. This research method uses a quasi-experimental method with a one group pretest-posttest design. The population in this study were female students of SMK TRIS Maros with a sample of 20 respondents using a sampling technique of purposive sampling. The results of the study showed a difference before and after dysmenorrhea exercises in the morning of -3.804 and a difference before and after dysmenorrhea exercises in the afternoon of -5.239, thus dysmenorrhea exercises in the afternoon are more effective than dysmenorrhea exercises in the morning in reducing menstrual pain during menstruation with a p value of 0.000. It is expected that health workers will provide counseling or health promotion about women's reproductive health, especially the management of dysmenorrhea with dysmenorrhea exercises as a non-pharmacological therapy that does not have a negative impact on the body.